The effect of glycemic control on sleep quality in type 2 diabetes mellitus - Koç, Zeynep; Böyük, Banu; Akın, Seydahmet; Keskin, Özcan; Aladağ, Nazire (The European Research Journal, 2023)
Objectives: There are publications showing sleep quality is impacted in type 2 diabetes mellitus (T2DM) cases. In our study, we planned to assess the prevalence of sleep disorder in these patients compared to society, and investigate whether poor glycemic regulation and increased body mass index (BMI) caused disruption of sleep quality or not. Methods: Sleep quality was compared between patients followed in our clinic with T2DM (n = 534) for minimum 5 years and a control group (n = 269). Assessment was performed for whether increased glycated haemoglobin (HbA1c) and increased BMI caused an increase in Pittsburgh Sleep Quality Index (PSQI) score or not. Cases with any comorbid disease or drug use affecting sleep quality were excluded from the study. Results: T2DM patients had higher PSQI points compared to the control group. A statistically significant, very low-level positive correlation was identified between BMI measurements and PSQI scores (as BMI increased, PSQI increased). A statistically significant, very low-level positive correlation was identified between HbA1c measurements and PSQI scores (as HbA1c increased, PSQI increased). HbA1c measurements of those in the good sleep quality group were significantly lower compared to those in the moderate sleep quality and poor sleep quality groups. The BMI measurements in the poor sleep quality group were significantly higher than those in the good sleep quality group. Conclusions: The sleep quality of T2DM cases was worse compared to the control group, while the increase in HbA1c level further disrupted sleep quality. The increase in BMI is another factor disrupting sleep quality in diabetic patients.